MENGUKUR LAJU AIR KELUAR DARI BOTOL PADA TIAP LUBANG DENGAN KETINGGIAN TERTENTU - Asmawati, Eka Yulisari (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
Experiments have been conducted to measure the rate of water out of the bottle on each hole with a certain height. The research method is to perform a simple test. Tests carried out using perforated by nails bottles are heated / solder. When it was acquired 5 hole will be closed by the bottle duct tape / plaster. Then bottle filled with water to the brim, open the first hole, then count the time the water out of the hole, this step is done repeatedly until the fifth hole. After the results of the data obtained will be used widely calculation formula bottle (A=Â Ïd2Â ), water discharge (Q = Â ) and the rate of water (v = ). The results of these calculations found that the fourth hole or holes which position has the lowest rate of water faster than others. This is because in the lowest position, they experienced greater pressure than the top position. So, with tremendous pressure to make the flow of fluid to flow faster.